Бешеная: роман / А. А. Бушков - Бушков Александр Александрович (Русский проект, 1999)
Экземпляры: Селтинская районная библиотека (аб) (20190830) / Инвентарный номер: 193329 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6